2020
DOI: 10.1109/access.2020.3013016
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Self-Perception in Mixed Reality: Egocentric Arm Segmentation and Database With Automatic Labeling

Abstract: In this study, we focus on the egocentric segmentation of arms to improve self-perception in Augmented Virtuality (AV). The main contributions of this work are: i) a comprehensive survey of segmentation algorithms for AV; ii) an Egocentric Arm Segmentation Dataset (EgoArm), composed of more than 10, 000 images, demographically inclusive (variations of skin color, and gender), and open for research purposes. We also provide all details required for the automated generation of groundtruth and semi-synthetic imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 66 publications
0
24
0
Order By: Relevance
“…From this AMT-based labeling experiment we found of special relevance that: i) better results were obtained from Turks who hold Master Qualification; and ii) instructors checked themselves that boundaries were precise enough and classes were corrected 5 . If images were not correctly processed, instructors rejected the tasks, providing detailed feedback.…”
Section: Thu-read Segmentation Labelingmentioning
confidence: 99%
See 3 more Smart Citations
“…From this AMT-based labeling experiment we found of special relevance that: i) better results were obtained from Turks who hold Master Qualification; and ii) instructors checked themselves that boundaries were precise enough and classes were corrected 5 . If images were not correctly processed, instructors rejected the tasks, providing detailed feedback.…”
Section: Thu-read Segmentation Labelingmentioning
confidence: 99%
“…To achieve this, one has to move to- wards deep learning approaches, and more in particular to semantic segmentation networks. In this line, Gonzalez-Sosa et al explore state-of-the-art networks for segmenting egocentric human body parts [5] using a semi-synthetic dataset. The reported results suggest suggested that semantic segmentation networks can overcome some of the limitations of color-based solutions, as now networks incorporate more complex information than just color, or of depth-based solutions, specially in outdoors scenarios.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Fully immersive applications must provide the users with a high sense of embodiment and presence [21], which requires complex algorithms such as hand tracking or egocentric human segmentation [12]. The theoretical network requirements, in terms of latency and downlink and uplink throughput, for successfully ofoading some or all of these and other complex algorithms in diferent scenarios are proposed in [22].…”
Section: Introductionmentioning
confidence: 99%